The 100th Anniversary of the Russian Revolution of 1917 – the Historical Memory Formation in Contemporary Situation: Столетие революции 1917 года в России – формирование исторической памяти в современной ситуации - Kucheryavaya, Elena V. (Przegląd Wschodnioeuropejski, 2020)
The article presents selected outcomes of the international research project “From the Enemy of the People to New Martyr”, investigating the memory of the Russian Revolution of 1917 and of the Great Terror, and its place in contemporary discourse in Russia. The research is sponsored by the Polish National Science Centre and is conducted at the Maria Grzegorzewska Pedagogical University in Warsaw (2017-2020 years). The one of the project’s stages was the investigation of shaping the historical memory by authorities in contemporary Russia, conducted with using research method of discourse analysis in 2017 year. The results of the analysis of the public discourse demonstrate how the perception of the Revolution of 1917 changes in Russia nowadays, and how in the year of the 100th anniversary new understanding of the historical events are being shaped. It also demonstrates the impact of the contemporary political situation on the creation of new discourse about Revolution.